Analisis Perlindungan Hukum Anak terhadap Kejahatan Kekerasan Seksual - Defika Yulita Nirmalasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Sexual violence against children is a crucial issue in Indonesia, with the number of cases continuing to increase. This research evaluates the effectiveness of legal protection based on Law no. 35 of 2014 and Law no. 23 of 2004. Data for 2024 shows an increase in cases of child sexual violence by 15% from the previous year, with a total of 4,500 cases. The main obstacles in implementing legal protection include a lack of special training for law enforcers, limited budgets, weak inter-agency coordination, and social stigma that inhibits reporting. Comprehensive psychosocial support, such as therapy and rehabilitation, has proven crucial for victims' recovery. Suggestions for improving legal protection include increasing training, better budget allocation, improving institutional coordination, reducing social stigma, and strengthening the role of communities and non-governmental organizations. With these steps, it is hoped that legal protections can be strengthened, ensuring children grow up in a safe and supportive environment.